Pressure filtration and slip casting of mixed alumina–zircon suspensions - Garrido, Liliana Beatriz (2001)
Mullite-zirconia based ceramics can be obtained from zircon raw material and alumina. Rheological properties of aqueous 48 vol.% suspensions containing a mixture of zircon and α-alumina powders were determined to obtain the optimum dispersion conditions for colloidal processing of dense mullite–zirconia composites. Powder compositions with different alumina/zircon (wt.% ) ratios in the mixtures were studied. Colloid stability as a function of pH for zircon and alumina, with and without polyacrylate, was studied by sedimentation tests. The effect of the chemical composition of the mixed powders and addition of polyacrylate on the viscosity of the suspensions were examined. Green density of compacts that were consolidated by slip casting and pressure filtration at 8 MPa were correlated with rheological properties of the suspensions and their compositions. Pressure filtered bodies were slightly less dense than the compacts prepared by slip casting and the dried relative density increased with increasing the degree of dispersion of the particles. After sintering at 1600°C for 2 h, the compacts from well-dispersed suspensions reached high density showing a fine and homogeneous microstructure.